2009
DOI: 10.1002/app.29588
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a plasticizer on the structure of biodegradable starch/clay nanocomposites: Thermal, water‐sorption, and oxygen‐barrier properties

Abstract: In this study, we investigated nanocomposites based on a plasticized natural biodegradable matrix. The polymer used was a natural potato starch, and the plasticizers were glycerol and a urea/ethanolamine mixture. A natural and an organically modified montmorillonite were studied. Two series of films containing 6 wt % nanoclays were prepared by a solution/cast process: the first series was based on neat starch, and the second one was based on 20 wt % plasticized starch. For all matrices, a mixture of intercalat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
93
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(109 citation statements)
references
References 54 publications
11
93
1
4
Order By: Relevance
“…22,23 This phenomenon was less intense in the samples containing 30% PLA (M3025 and M3030) which is consistent with these samples having a less hydrophilic character.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…22,23 This phenomenon was less intense in the samples containing 30% PLA (M3025 and M3030) which is consistent with these samples having a less hydrophilic character.…”
Section: Resultssupporting
confidence: 78%
“…This behavior has been reported by other authors working with hydrophilic polymers plasticized with polyols and is associated with increased amounts of hydroxyl groups from the plasticizer. 20,22,23 This increase causes an increase in the hygroscopicity of the material, reflected in the increase in the solubility coefficient of the samples with higher glycerol concentration.…”
Section: Resultsmentioning
confidence: 99%
“…As kaolin content increased, OP decreased significantly. The incorporation of nanoparticles into the matrix could likely introduce a tortuous pathway for oxygen molecules to pass through, and the reduction in permeability coefficients means that gases should travel this longer diffusive path (Zeppa et al 2009;Nafchi et al 2013). Also reported similar OP results with the incorporation of nanoparticles (Bae et al 2009;Türe et al 2013).…”
Section: Permeability To Oxygenmentioning
confidence: 99%
“…Several other studies showed no improvement on the thermal properties of starch/clay composites in comparison to TPS. 20,44,45 The first derivative of TGA curves of TPS and Star/Vee-Chit 5.0% nanocomposite are shown in Supporting Information, Figure S2. …”
mentioning
confidence: 99%